Silicon-graphene-graphite composite material

By mixing silicon particles with peelable graphene material and grinding under high shear force to form nanoparticles, encapsulate them in the graphene layer, and introducing graphite at the same time, the volume expansion and cyclic performance problems of the silicon anode material of lithium-ion batteries are solved, achieving high capacity and good cyclic stability.

CN119947986APending Publication Date: 2025-05-06ARCELORMITTAL SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280100485.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The silicon anode materials of existing lithium-ion batteries have huge volume expansion, low conductivity, poor cycling performance and low Faraday efficiency in the first cycle, resulting in deterioration of the electrode structure and increased interfacial stress.

Method used

Nanoparticles are formed by mixing silicon particles with peelable graphene material and grinding under high shear forces, encapsulating in the graphene layer while graphite is introduced to improve conductivity and buffer volume fluctuations.

Benefits of technology

The high capacity of the silicon anode material, good cycling stability and improved Faraday efficiency are achieved, reducing the mechanical stress and interface fracture of the electrode structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005329583600000131
    Figure BDA0005329583600000131
  • Figure BDA0005329583600000142
    Figure BDA0005329583600000142
  • Figure BDA0005329583600000151
    Figure BDA0005329583600000151
Patent Text Reader

Abstract

The present invention relates to a method of manufacturing a silicon-graphene-graphite composite for a silicon-based anode of a lithium ion battery, the method comprising: aggregating silicon particles having a particle size distribution D10 greater than 100 nm and a peelable graphene-based material together in a first organic solvent, the weight ratio of silicon to the peelable graphene-based material is from 1.5 to 9; mixing at least 500 rpm for at least 20 minutes to grind the silicon particles into nanoparticles, exfoliating at least a portion of the exfoliable graphene-based material into graphene and forming a silicon-graphene composite; aggregating the silicon-graphene composite and graphite together, the weight ratio of carbon to silicon being from 1.5 to 19, and the viscosity being from 0.025 Pa.sec to 160 Pa.sec at a shear rate of 1 se-1; and mixing for at least 2 minutes to form the silicon-graphene-graphite composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a silicon-graphene-graphite composite material for a silicon-based anode of a lithium-ion battery. The present invention also relates to a method for producing the silicon-graphene-graphite composite material and its active material. Background Art

[0002] A typical lithium-ion battery consists of a carbon-based anode (e.g., graphite), a lithium metal oxide-based cathode (e.g., LiCoO2), and a carbonate-based organic electrolyte (e.g., ethylene carbonate (EC), dimethyl carbonate (DMC)) with a lithium salt (e.g., LiPF6). Energy is stored in the electrodes in the form of Li-intercalation compounds (LICs). During discharge and charge, Li + Ions are intercalated and deintercalated between graphite (anode) and LiCoO2 (cathode) through the electrolyte.

[0003] Carbon / graphite is the active material of choice for the anode. It has the ability to intercalate lithium into the structure with a small amount of expansion. However, graphite-based anodes produce limited specific capacity (372 mA hg -1 ) and some key issues include Li plating, which leads to dendrite formation.

[0004] As a promising anode material for lithium-ion batteries, silicon has many advantages over graphite, such as very high capacity, wide availability, good stability, and environmental friendliness. In particular, it has the highest gravimetric capacity (4200 mA h g) superior to lithium metal. -1 , Li is absorbed into Li 22 Si5 stoichiometry) and volumetric capacity (9786 mA h cm -3 , based on the initial volume of Si).

[0005] However, certain obstacles prevent the use of silicon, namely, huge volume expansion, low electrical conductivity, poor cycling performance, and low Faradaic efficiency in the first cycle. In particular, the volume expansion during Li-alloying (for Li 22 Si5 is about 360%), which generates huge mechanical stress during repeated charging and discharging, leading to a series of serious destructive consequences: the gradually enhanced pulverization during repeated lithiation / delithiation cycles deteriorates the electrode structure; the interfacial stress cuts off the electrical connection between the active material and the current collector; and the continuous formation-rupture-reformation of the solid electrolyte interface (SEI) film continuously consumes electrolyte and lithium ions.

[0006] One strategy to overcome the above limitations of Si anode materials includes constructing an effective conductive network and an external buffer against Si volume fluctuation by combining Si with a secondary phase (e.g., carbon, metal, ceramic, and carbon-based compounds such as graphene and its derivatives).

[0007] It is particularly known from H. Xiang, K. Zhang, G. Ji, JY Lee, C. Zou, X. Chen, J. Wu, Graphene / nanosized silicon composites for lithium battery anodes with improved cycling stability, Carbon 49 (2011) 1787-1796 to blend nanosized Si particles with graphene sheets prepared by high temperature (1050° C.) thermal expansion of graphite.

[0008] Better than the simple fabrication of binary Si / graphene hybrids, incorporation of additional carbon phases (such as graphite or amorphous carbon) has been demonstrated to be another effective way to enhance the cycling stability of Si-based anodes.

[0009] It is particularly known from CCHsieh, WRLiu, Carbon-coated Si particles binding with few-layered graphene via a liquid exfoliation process as potential anode materials for lithium-ion batteries, Surf.Coating.Technol.387(2020)125553 that Si / few layer graphene / C composites (Si / FLG / C) are prepared by a) ultrasonically treating a mixture of Si powder, few layer graphite and pitch (as a carbon precursor) in acetone until the solvent evaporates, b) drying in an oven at 80°C for 1 hour to remove residual solvent, c) calcining at 1000°C for 2 hours at a rate of 5°C / min under an argon flow.

[0010] However, the fabrication of Si-based anodes with high mass loading and high areal capacity via scalable, simple, and environmentally friendly techniques remains an unsolved problem. Summary of the invention

[0011] It is therefore an object of the present invention to remedy the disadvantages of the prior art by providing an efficient method for producing silicon-graphene composite materials.

[0012] To this end, a first object of the present invention comprises a method for producing a silicon-graphene-graphite composite material for a silicon-based anode of a lithium-ion battery, comprising:

[0013] -(i) Supply particle size distribution D 10 Silicon particles larger than 100 nm, exfoliable graphene-based materials comprising at least 85 wt. % carbon,

[0014] - (ii) aggregating silicon particles and an exfoliable graphene-based material together in a first organic solvent, the weight ratio of silicon to the exfoliable graphene-based material being 1.5 to 9,

[0015] - (iii) mixing the composition of step (ii) at at least 500 rpm for at least 20 minutes to grind the silicon particles into nanoparticles, to exfoliate at least a portion of the exfoliable graphene-based material into graphene and to form a silicon-graphene composite material,

[0016] - (iv) bringing together a silicon-graphene composite material and graphite, the weight ratio of carbon from both the graphene and the graphite to silicon being between 1.5 and 19, and the viscosity being between 1 second and 200°C. -1 The shear rate is 0.025Pa·s to 160Pa·s,

[0017] - (v) mixing the composition of step (iv) for at least 2 minutes to form a silicon-graphene-graphite composite material.

[0018] The method according to the invention may also have the optional features listed below, considered individually or in combination:

[0019] - the exfoliable graphene-based material is selected from graphite, intercalated graphite, expanded graphite, graphite oxide, reduced graphite oxide, graphene oxide, reduced graphene oxide and mixtures thereof,

[0020] - the first organic solvent is selected from isopropanol, ethanol and mixtures thereof,

[0021] - the weight ratio of silicon to the first organic solvent is less than 0.66,

[0022] - Step ii) and step iii) are performed simultaneously,

[0023] - At the end of step iii), the particle size distribution D of the Si particles 50 Up to 70nm,

[0024] - The graphite of step iv) has a particle size distribution D below 20 μm 90 and particle size distribution D below 10 μm 50 ,

[0025] - the graphite of step iv) is battery grade graphite,

[0026] - adding a second solvent during step iv),

[0027] - in step iv) and step v), the solid content is kept above 11%,

[0028] - in step v), the graphite is not exfoliated,

[0029] - in step v), the mixing lasts for less than 20 minutes,

[0030] - the method further comprises a step (vi) of evaporating the solvent from the silicon-graphene-graphite composite material to dry the silicon-graphene-graphite composite material,

[0031] - The method further comprises the step vii) of heat treating the silicon-graphene-graphite composite material under an inert atmosphere.

[0032] A second object of the present invention comprises a silicon-graphene-graphite composite material for a silicon-based anode of a lithium-ion battery, comprising:

[0033] - Particle size distribution D wrapped in graphene layer 50 Silicon particles up to 70nm in size,

[0034] - graphite particles having a weight ratio of carbon to silicon of 1.5 to 19,

[0035] - a first organic solvent,

[0036] Viscosity of silicon-graphene-graphite composites in 1 second -1 The shear rate is 0.025 Pa·s to 160 Pa·s.

[0037] A third object of the present invention includes an active material for a silicon-based anode of a lithium-ion battery, comprising a silicon-graphene-graphite composite material, the silicon-graphene-graphite composite material comprising:

[0038] - Silicon particles with a particle size distribution D50 up to 70 nm encapsulated in graphene layers,

[0039] - Graphite particles having a carbon to silicon weight ratio of 1.5 to 19.

[0040] A fourth object of the invention consists in a silicon-based anode for a lithium-ion battery comprising an active material according to the invention.

[0041] A fifth object of the invention consists of a lithium-ion battery comprising a silicon-based anode according to the invention.

[0042] It is evident that the present invention is based on, on the one hand, a first mixing step of simultaneously grinding the Si particles into nanoparticles, exfoliating at least a portion of the exfoliable graphene-based material into graphene and wrapping the Si particles in graphene layers to form a composite material, and on the other hand, a careful control of the viscosity during a second mixing step, wherein graphite is further introduced into the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Further features and advantages of the present invention will be described in more detail in the following description.

[0044] The present invention will be better understood by reading the following description with reference to the following, which is provided for purposes of illustration only and is not intended to be limiting in any way:

[0045] - Figure 1 , which is a SEM image of a two-phase mixture of silicon particles and exfoliable graphene-based material mixed at 3350 rpm for 15 minutes,

[0046] - Figure 2 , which is a SEM image of the silicon-graphene composite material according to the present invention,

[0047] - Figure 3 , which is a SEM image of the silicon-graphene composite material according to the present invention,

[0048] - Figure 4 , which is an EDX analysis of a two-phase mixture of silicon particles and exfoliable graphene-based material mixed at less than 500 rpm for 30 minutes,

[0049] - Figure 5 , which is an EDX analysis of the silicon-graphene composite material according to the present invention. DETAILED DESCRIPTION

[0050] Nanoparticles are defined as particles with a size distribution D 50 Particles below 100nm.

[0051] In the first step (step i), a particle size distribution D is supplied 10 Silicon particles larger than 100 nm and an exfoliable graphene-based material comprising at least 85 wt. % carbon.

[0052] Particle size distribution of Si particles D 10 Greater than 100 nm, i.e. they are not nanoparticles. Avoiding nanoparticles as raw materials makes the handling of raw materials safer. Grinding Si particles during mixing with the exfoliable graphene-based material is also more energy efficient than grinding Si particles before mixing.

[0053] The Si particles preferably have a size in the submicron range. More preferably, the particle size distribution D 90 Even more preferably, D 90 This particle size distribution improves the yield of mixing, i.e., the Si particles are effectively ground while being mixed with the exfoliable graphene-based material without requiring much energy for mixing.

[0054] The shape of Si particles is not limited. They may be spherical or irregular.

[0055] The purity of the Si particles is preferably at least 98 wt %, preferably at least 99.9 wt %. High purity Si particles improve the performance of the electrode and thus the performance of the lithium ion battery. The Si may contain impurities such as Al, Ca, Fe, Ti, P, Cu, Cr, K, V, Ni, SiO2 and Na.

[0056] The Si particles are preferably crystalline. This improves the performance of the electrode and thus the performance of the lithium-ion battery.

[0057] The Si particles may be provided in an organic solvent. This prevents oxidation of the silicon particles during transport and storage. Any organic solvent offers this advantage and may be used for this purpose. Having said that, alcohols are preferred because they have a low boiling point and further improve the dispersion of the Si particles. More preferably, the organic solvent is selected from isopropanol, ethanol and mixtures thereof.

[0058] Strippable graphene-based materials mean that the material is based on a graphene layer that can be stripped or further stripped, i.e., based on a monolayer of carbon atoms arranged in a two-dimensional honeycomb lattice nanostructure. There is no restriction on the way the graphene layers of the strippable graphene-based material are stacked. It can be ABA stacking or ABC stacking. The graphene layers can be intercalated or expanded or partially stripped in the form of a monolayer, a double layer and / or several layers.

[0059] Examples of possible exfoliable graphene-based materials are graphite, intercalated graphite, expanded graphite, graphite oxide, reduced graphite oxide, graphene oxide, reduced graphene oxide.

[0060] The exfoliable graphene-based material is preferably in the form of graphite. The graphite may be natural or synthetic. It may be Kish graphite.

[0061] The exfoliable graphene-based material comprises at least 85 wt. % carbon, preferably at least 97 wt. %, more preferably at least 99 wt. %, which improves the performance of the electrode and thus the performance of the lithium-ion battery.

[0062] The particle size distribution of the exfoliable graphene-based material is not limited. If the same material is used for step iii) and step iv), a particle size distribution D is preferably used. 90 For particles with a maximum size of 20 μm. Otherwise, the size distribution D 90 Particles up to 250 μm or 500 μm.

[0063] The exfoliable graphene-based material is preferably in the form of nanosheets, ie nano-objects with one outer dimension being nanoscale and the other two outer dimensions being significantly larger and not necessarily nanoscale. This facilitates the exfoliation of the exfoliable graphene-based material and thus facilitates the encapsulation of the Si particles.

[0064] The exfoliable graphene-based material is preferably not partially exfoliated, more preferably not exfoliated. This makes the manufacturing more energy efficient, because the exfoliable graphene-based material will only be exfoliated during the process according to the invention, and it does not have to be exfoliated before the process.

[0065] In the second step (step ii), silicon particles and the exfoliable graphene-based material are aggregated together in a first organic solvent.

[0066] After the exfoliable graphene-based material has been exfoliated or further exfoliated, the organic solvent prevents oxidation of the silicon particles, prevents agglomeration of the silicon particles, and prevents restacking of the graphene layers. Thus, the organic solvent helps to obtain a uniform mixture.

[0067] Any organic solvent offers these advantages and can be used for this purpose. Having said that, alcohols are preferred because they have a low boiling point and further improve the dispersion of Si particles. More preferably, the organic solvent is selected from isopropanol, ethanol and mixtures thereof. For clarity, water is not considered an organic solvent.

[0068] The first organic solvent may be an organic solvent that can disperse silicon particles therein when supplied in step (i).

[0069] The weight ratio of silicon to the strippable graphene-based material is from 1.5 (which corresponds to 60 wt. % silicon and a ratio of 60:40) to 9 (which corresponds to 90 wt. % silicon and a ratio of 90:10). This range is important for achieving suitable performance of the electrode and therefore of the lithium-ion battery. Below 1.5, an excess of the strippable graphene-based material is stripped during the process, which reduces the performance of the battery, in particular the Coulombic efficiency. Above 9, there is not enough graphene to wrap the silicon particles. Therefore, the volume expansion of silicon during Li-alloying is not properly buffered by graphene, and the active material cannot benefit from the high conductivity of graphene.

[0070] The weight ratio of silicon to exfoliable graphene-based material is preferably 3 to 6, which further improves performance.

[0071] The weight ratio of silicon to organic solvent is preferably less than 0.66 (corresponding to 40% by weight of silicon and a ratio of 40:60) to further prevent oxidation of Si particles and facilitate mixing. The weight ratio of silicon to organic solvent is preferably at least 0.05 (corresponding to 5% by weight of silicon and a ratio of 5:95) to promote the encapsulation of Si particles in graphene and accelerate the evaporation of organic solvent at the end of the process. Limiting the amount of organic solvent also prevents Si particles and exfoliable graphene-based materials (or graphene obtained from the material) from settling in the solvent. More preferably, the weight ratio of silicon to organic solvent is 0.11 (corresponding to 10% by weight of silicon and a ratio of 10:90) to 0.43 (corresponding to 30% by weight of silicon and a ratio of 30:70), which further promotes the process.

[0072] The solid content is preferably at least 6%, more preferably at least 20%, even more preferably 20% to 30%. It prevents the Si particles and the exfoliable graphene-based material (or the graphene obtained therefrom) from settling in the solvent. In addition, it facilitates the next steps.

[0073] Preferably, in step (ii), no other ingredients are aggregated together except the silicon particles, the exfoliable graphene-based material and the organic solvent. No additional ingredients are required to achieve the desired properties of the electrode and thus the desired properties of the lithium-ion battery.

[0074] In the third step (iii), silicon particles, an exfoliable graphene-based material and a first organic solvent are mixed to form a silicon-graphene composite material in the first organic solvent. This composite material is equivalent to Si nanoparticles wrapped in graphene layers.

[0075] Mixing is performed at at least 500 rpm to generate high shear forces, which simultaneously:

[0076] - Grinding Si particles into nanoparticles,

[0077] - exfoliating at least a portion of the exfoliable graphene-based material into graphene,

[0078] - Wrapping Si particles in graphene layers.

[0079] In particular, Si particles are inserted between graphene layers, which facilitates the exfoliation of exfoliable graphene-based materials. In addition, wrapping Si particles in graphene layers prevents agglomeration of Si particles or restacking of graphene.

[0080] Below 500rpm, the shearing of the mixture is insufficient to have proper grinding, exfoliation and wrapping. Therefore, two phases remain, and the mixture is not a composite material. At 500rpm, a silicon-graphene composite material is formed. At higher mixing speeds, the exfoliable graphene-based material can be further exfoliated. It further buffers the volume expansion of silicon during Li-alloying, and thus further improves the life of the battery.

[0081] Preferably, the mixing speed is from 1000 rpm to 8000 rpm, more preferably from 2500 rpm to 6000 rpm.

[0082] The mixing is carried out during at least 20 minutes. In the case of a shorter duration, the Si particles do not have enough time to be ground and incorporated into the graphene obtained from the exfoliable graphene-based material.

[0083] In case of longer mixing duration, the exfoliable graphene-based material can be further exfoliated, which further buffers the volume expansion of silicon during Li-alloying and thus further improves the battery life.

[0084] Preferably, the mixing duration is from 25 minutes to 1 hour.

[0085] The mixing is preferably carried out in a high shear mixer. The mixing is preferably carried out in a rotor-stator mixer (also called an impeller mixer). The mixer may in particular be a blade mixer, a sawtooth blade mixer or a paddle mixer.

[0086] Step ii) and step iii) can be performed simultaneously. In other words, mixing can be started before all raw materials have been added to the mixture. For example, silicon particles and organic solvent can be first brought together and mixed. Then the exfoliable graphene-based material can be added stepwise.

[0087] Step iii) may comprise a single mixing step or a plurality of sequential mixing steps. In the latter case, the exfoliable graphene-based material may be better exfoliated.

[0088] At the end of this step, the Si nanoparticles preferably have a size distribution D up to 70 nm. 50 This further improves the buffering of the volume expansion of silicon during Li-alloying and thus improves the performance of the cell.

[0089] The graphene obtained from the exfoliation of the exfoliable graphene-based material is not limited to a single layer of carbon atoms. It includes single-layer graphene, double-layer graphene and few-layer graphene. It can also be partially oxidized.

[0090] At the end of this step, a silicon-graphene composite material is obtained. Since a portion of the strippable graphene-based material may not be stripped or not completely stripped to graphene, the silicon-graphene composite material may contain a portion of the strippable graphene-based material. In this specification, the term "silicon-graphene composite material" refers to a composite material comprising silicon, graphene as defined above and possibly a strippable graphene-based material.

[0091] The silicon-graphene composite material comprises silicon particles with a particle size distribution D50 of up to 70 nm wrapped in a graphene layer. In particular, the silicon-graphene composite material comprises silicon particles with a particle size distribution D50 of up to 70 nm wrapped in a graphene layer from a graphene-based material. The weight ratio of silicon to the graphene-based material is 1.5 to 9. More particularly, the silicon-graphene composite material comprises silicon particles with a particle size distribution D50 of up to 70 nm wrapped in a graphene layer peeled off from a peelable graphene-based material. The weight ratio of silicon to the peelable graphene-based material is 1.5 to 9.

[0092] In the fourth step (step iv), the previously obtained silicon-graphene composite material in the first organic solvent is aggregated with graphite.

[0093] Adding graphite to the silicon-graphene composite improves the conductivity of the active material and, therefore, the performance of the battery.

[0094] The graphite contains preferably more than 99% Cg to further improve the performance of the battery. Cg means carbon in the form of graphite, rather than carbon atoms bound in the molecular structure of other minerals. The graphite is in the form of particles. It can be in the form of nanosheets or spheres. The graphite particles preferably have a particle size distribution D below 20 μm. 90 and particle size distribution D below 10 μm 50 .

[0095] Typical graphites for lithium-ion batteries include (1) natural graphite, (2) graphitized mesophase carbon or microspheres formed by graphitization of mesophase pitch materials, (3) hard carbon formed by pyrolysis of polymer materials, and (4) natural or artificial graphite materials that may be coated with a hard carbon surface layer or a soft carbon surface layer. It may also be Kish graphite in particular.

[0096] The graphite is more preferably battery-grade graphite, also known as spherical graphite (SpG). It can be made from flake graphite concentrate produced by graphite ore. In the first step, the method includes micronizing, rounding and purifying flake graphite to produce uncoated SpG (uSpG). Micronizing includes reducing the size of the flakes to about 10 microns to 15 microns. The rounding or spheroidizing process reduces the surface area to make more graphite into a smaller volume. This creates a smaller, denser and more efficient anode product for the battery. It also increases the rate at which the battery can be charged and discharged. The micronized and rounded material is then purified to about 99.95% Cg using hydrofluoric acid and sulfuric acid. In the second step, the spheres can be coated with a thin layer of asphalt or asphalt and baked at above 1,200°C. This covers the uSpG with a hard carbon shell, thereby protecting the spheres from peeling and degradation during expansion and contraction under charge and discharge. It also inhibits the ongoing reaction of the electrolyte with the active graphite inside the spheres themselves.

[0097] The weight ratio of graphite to the silicon-graphene composite is adjusted so that the weight ratio of carbon to silicon is within the range specified below.

[0098] The weight ratio of carbon to silicon is from 1.5 (which corresponds to 40% silicon and a ratio of 60:40) to 19 (which corresponds to 5% silicon and a ratio of 95:5). The term "weight of carbon" refers to the weight of carbon from all carbon sources (except the solvent). The carbon sources are the graphene obtained in the third step, the graphite added in this step, and the part of the possible exfoliable graphene-based material that is not exfoliated or not completely exfoliated into graphene. Taking into account the purity of the exfoliable graphene-based material, it can be considered that the weight of carbon is the sum of the weight of the exfoliable graphene-based material added in the second step and the weight of the graphite added in this step.

[0099] Below 1.5, there is not enough carbon to buffer the volume expansion of silicon during Li-alloying. Above 19, the small amount of added silicon does not provide enough capacity improvement for the battery. More preferably, the carbon to silicon ratio is 1.86 (which corresponds to 35% silicon and a ratio of 65:35) to 9 (which corresponds to 10% silicon and a ratio of 90:10). This further improves the performance of the battery.

[0100] Viscosity of the Si-graphene / graphite / solvent mixture at 1 s -1 The viscosity of the mixture is preferably between 0.025 Pa·s and 160 Pa·s at a shear rate of 1.5-2.0. This viscosity allows obtaining a silicon-graphene-graphite composite material in a unique phase. It also prevents oxidation of Si particles. The viscosity of the mixture is preferably between 1 and 2.5 Pa·s and 1.5 Pa·s. -1 The shear rate is 0.4 Pa·s to 50 Pa·s, more preferably 1 second. -1The shear rate is 1 Pa·s to 10 Pa·s, which further facilitates the suspension of graphite particles in the mixture and the homogeneity of the mixture.

[0101] The viscosity can be easily adjusted by adding a second solvent. Water or any organic solvent can be used for this purpose. Having said that, alcohols are preferred because they have a low boiling point and further improve the dispersion of Si particles. More preferably, the second solvent is an organic solvent selected from isopropanol, ethanol and a mixture thereof. The organic solvent may be the same as the first organic solvent of step (ii). It particularly facilitates waste management. Alternatively, the second solvent is a co-solvent of the first organic solvent, which helps to evaporate the solvent at a later stage. At this step, water is an option. Mixing has a limited duration, and the silicon particles wrapped in graphene will not oxidize. In addition, since water is used in the manufacturing process of the electrode, water does not have to evaporate from the silicon-graphene-graphite composite material before starting the manufacturing process of the electrode.

[0102] Typically, the minimum viscosity corresponds to a solid content of about 11%. Therefore, the solid content is preferably maintained above 11%. More preferably, the solid content is from 11% to 40%.

[0103] In the fifth step (step v), the silicon-graphene composite material, graphite, and a first organic solvent are mixed to form a silicon-graphene-graphite composite material.

[0104] The type of mixing is not limited. It may in particular be planetary mixing or mechanical mixing. Preferably, the mixing is performed so that there is no chance of graphite being exfoliated, which would reduce the performance of the active material. Therefore, the mixer preferably does not have any impeller, such as blades or paddles.

[0105] The materials are mixed for at least 2 minutes to obtain a homogenous mixture. The materials are preferably mixed for less than 20 minutes.

[0106] At the end of this step, a silicon-graphene-graphite composite material is obtained. As described with respect to the third step (step iii), during the third step, a part of the strippable graphene-based material may not be stripped or not completely stripped into graphene, and the silicon-graphene composite material may include a part of the strippable graphene-based material. Therefore, the silicon-graphene-graphite composite material may also include a part of the strippable graphene-based material. In this specification, the term "silicon-graphene-graphite composite material" refers to a composite material comprising silicon, graphene as defined above, graphite, and possible strippable graphene-based materials other than graphite.

[0107] The silicon-graphene-graphite composite material comprises the silicon-graphene composite material as obtained at the end of the third step, graphite particles (the weight ratio of carbon to silicon is 1.5 to 19) and a first organic solvent, and the viscosity of the silicon-graphene-graphite composite material is 100% by weight at 1 second. -1 The shear rate is 0.025 Pa·s to 160 Pa·s.

[0108] According to one variant of the invention, in a sixth step (step vi), the solvent is evaporated from the silicon-graphene-graphite composite material in order to dry the composite material and obtain the active material.

[0109] Evaporation of the solvent is only optional, since in industrial processing the active material may have to be dispersed in a solvent to make an ink for electrode fabrication.

[0110] Drying can be carried out in particular by spray drying, freeze drying or by rotary evaporation.

[0111] The active material can be assessed to be significantly dry by thermogravimetric analysis (TGA). In this case, no weight loss was observed at temperatures below 120°C.

[0112] In case the same organic solvent is used in step (ii) and step (iv), it can be reused at the end of the evaporation step to produce more active material. This limits waste.

[0113] According to one variant of the present invention, the active material is further heat treated under an inert atmosphere. It eliminates possible slight oxidation of Si particles and further improves the quality of graphite and graphene. It is worth noting that in the case where the exfoliable graphene-based material is in an oxidized form (particularly graphene oxide or reduced graphene oxide), the heat treatment under an inert atmosphere reduces or further reduces the material. The inert gas is preferably selected from hydrogen, argon, nitrogen and mixtures thereof. The temperature is preferably 700°C to 1500°C, more preferably 900°C to 1100°C. The shortest duration is preferably 30 minutes. The pressure can be atmospheric pressure or vacuum.

[0114] After obtaining the silicon-graphene-graphite composite material, it can be used as an active material for the silicon-based anode for manufacturing lithium-ion batteries. These anodes are composite electrodes. In addition to the active material, it also contains the following inactive materials: a binder that holds the electrode particles together, and an electronic conductive agent (i.e., carbon black) that increases electrical conductivity. They are usually mixed together to form ink or slurry to form a relatively uniform and stable coating on the current collector. Inactive materials do not directly participate in the electrochemical redox reaction, however, but they are important to the functionality of the entire electrode.

[0115] The binder is preferably a polymer binder. Commonly used polymer binders include polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose / styrene butadiene rubber (CMC / SBR), polyacrylate (PAA), lithium polyacrylate (LiPAA), polyvinyl alcohol (PVA), sulfonated tetrafluoroethylene-based fluoropolymer-copolymers (e.g. ), sodium alginate (SA), chitosan (CS), and guar gum (GG).

[0116] After the silicon-based anode is manufactured, it can be used to make lithium-ion batteries.

[0117] When the anode is first charged, it slowly approaches the lithium potential and begins to react with the electrolyte to form a film on the surface of the electrode. This film is made up of products produced by the reduction reaction of the anode with the electrolyte. This film is called the solid electrolyte interface (SEI) layer. Proper formation of the SEI layer is critical for good performance. Since the lithium in the battery comes from the lithium in the active cathode material, any loss due to the formation of the SEI layer will reduce the battery capacity. At the same time, the SEI layer protects the graphite surface from reacting with the electrolyte while providing Li + Passageways are provided into and out of the anode structure.

[0118] A lithium-ion battery based on an active material containing 16 wt. % silicone is considered sufficiently efficient if the First Coulombic Efficiency (FCE) is above 75%, the electrode charge capacity (measured after 10 cycles) is above 700 mAh / g, and the cyclability at 80% of the initial capacity retention is above 500 cycles.

[0119] A lithium-ion battery based on an active material containing 32 wt. % silicone is considered sufficiently efficient if the first coulombic efficiency (FCE) is above 65%, the electrode charge capacity (measured after 10 cycles) is above 1200 mAh / g, and the cyclability at 80% of the initial capacity retention is above 250 cycles.

[0120] Example

[0121] Example 1

[0122] Supply the following raw materials:

[0123] -12 g of 0.21 g / mL dispersed in isopropanol with a purity of more than 99% and a particle size distribution of D 90 Silicon particles below 291 nm, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0124] - 3 g of Kish graphite cleaned in a previous step to a purity of 99.9 wt. % C. Kish graphite has a particle size distribution D of 20 μm 90 .

[0125] Silicon particles and Kish graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 4 (80:20). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 5:95 to solvent and a solids content of 26%.

[0126] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 15 g of silicon-graphene composite material in 44.24 g isopropanol were obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0127] Then 15 g of silicon-graphene composite dispersed in 44.24 g of isopropanol was aggregated with 60 g of Kish graphite at a graphite / composite weight ratio of 4 (80:20), which corresponds to a carbon / silicon ratio of 5.25 (84:16). 120 mL of isopropanol was added to achieve a 1 second -1 Viscosity at shear rate of 152.16 Pa·s. Therefore, the solid content is 37%. The Kish graphite has been cleaned in a previous step to a purity of 99.9 wt. % C with a particle size distribution D of 20 μm 90 , 10μm particle size distribution D 50 and nanosheet shapes.

[0128] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-4 wt% graphene-80 wt% graphite composite.

[0129] To test the performance of this active material, it was mixed with lithium polyacrylate (LiPAA) and carbon black C45 in a ratio of 80:10:10 in water in a disperser Dispermat LC-30 at 5000 rpm for 1 hour. The obtained ink was then applied to a copper foil using a doctor blade to form a 100 μ thick wet coating. It was dried in a vacuum oven at 80 ° C for 12 hours. The dry coating was 70 μ thick.

[0130] Electrodes made from coated copper foil were tested in coin cells as half-cells against lithium under the following conditions:

[0131] - Electrolyte: 1 mol / L lithium hexafluorophosphate (LiPF6) in a solvent containing 3:7 volume ratio of fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) and 2 wt% vinylene carbonate (VC),

[0132] - Cycle Scheme:

[0133] ○ Relative to Li / Li + The SEI layer is formed by cycling once at a constant current at a rate of C / 20 in a voltage window of 0.01 V to 1.0 V, and then cycling 5 times at a constant current at a rate of C / 10.

[0134] ○ Cycle once at a constant voltage with a maximum current rate of C / 40, then cycle once at a constant voltage with a maximum current rate of C / 20.

[0135] ○ Repeated relative to Li / Li + The samples were cycled 24 times at a constant current rate of C / 2 in a voltage window of 0.01 V to 1.0 V and then at a constant current rate of C / 2 relative to Li / Li + The test piece was cycled once at a constant current at a rate of C / 10 in a voltage window of 0.01 V to 1.0 V, and once at a constant voltage at a maximum current rate of C / 10.

[0136] Where C is the battery capacity, i.e. the maximum amount of energy that can be extracted from the battery, expressed in ampere-hours (Ah).

[0137] Table 1 summarizes the obtained results:

[0138]

[0139]

[0140] Table 1

[0141] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0142] As can be seen, thanks to the composite material prepared with the method according to the invention, the electrode shows very good performances: 84% FCE, 824 mAh / g active material capacity and cyclability of 600 cycles.

[0143] Example 2

[0144] The difference between Example 2 and Example 1 is that the purity of C is higher than 97% by weight and the particle size distribution is D 90Reduced graphene oxide (rGO) of 10 μm and flake shape replaces Kish graphite as an exfoliable graphene-based material. In addition, graphite is mixed with a silicon-graphene composite material instead of Kish graphite.

[0145] Silicon particles and rGO in isopropanol were aggregated together at a weight ratio of silicon / rGO of 4 (80:20). This was done without further addition of isopropanol. Thus, the weight ratio of the exfoliable graphene-based material to solvent was 5:95, and the solid content was 26%.

[0146] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 4 g of silicon-graphene composite material in 20 g of isopropanol was obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0147] Then 4 g of silicon-graphene composite material dispersed in 20 g of isopropanol was mixed with 16.3 g of graphite (purity 99.9 wt % C, D 90 20μm, D 50 10 μm, nanoplatelet shape, supplied by Imerys) were aggregated at a graphite / composite weight ratio of 4 (80:20), which corresponds to a carbon / silicon ratio of 5.25 (84:16). 40 mL of isopropanol was added. Thus, the solid content was 28%.

[0148] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-4 wt% graphene-80 wt% graphite composite.

[0149] The obtained 16 wt % organosilicon-4 wt % graphene-80 wt % graphite composite material was tested under the same conditions as in Example 1.

[0150] Table 2 summarizes the results obtained:

[0151]

[0152] Table 2

[0153] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0154] As can be seen, the electrode shows very good performances, such as a FCE of 80% and a capacity of 723 mAh / g active material, due to the composite material prepared by the method according to the present invention.

[0155] Example 3

[0156] The difference between Example 3 and Example 1 is that 3 g of C with a purity of 99 wt% and a particle size distribution of D is used. 90 Expanded graphite (EG) with a particle size of 20 μm was used instead of Kish graphite. The mixing conditions were also different.

[0157] Silicon particles and expanded graphite in isopropanol were brought together in a silicon / graphite weight ratio of 4 (80:20). This was done by adding 77 g of isopropanol. Thus, the weight ratio of silicon to organic solvent was 7:93, the weight ratio of exfoliable graphene-based material to solvent was 2:98, and the solid content was 8%.

[0158] The composition was high shear mixed in a Silverson L5 mixer at 3000 rpm for 30 minutes. 15 g of silicon-graphene composite material in 132.43 g isopropanol was obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0159] 15 g of the silicon-graphene composite material dispersed in 132.43 g of isopropanol were then aggregated with 60 g of Kish graphite in a graphite / composite weight ratio of 4 (80:20), which corresponds to a carbon / silicon ratio of 5.25 (84:16). No isopropanol was added. The solid content was therefore 36%. The Kish graphite had been cleaned in a previous step to a purity of 99.9 wt. % C, having a particle size distribution D of 20 μm. 90 , 10μm particle size distribution D 50 and nanosheet shapes.

[0160] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-4 wt% graphene-80 wt% graphite composite.

[0161] The obtained 16 wt % organosilicon-4 wt % graphene-80 wt % graphite composite material was tested under the same conditions as in Example 1.

[0162] Table 3 summarizes the obtained results:

[0163]

[0164] Table 3

[0165] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0166] As can be seen, the electrode shows very good performances, such as a FCE of 84% and a capacity of 714 mAh / g active material, thanks to the composite material prepared with the method according to the present invention.

[0167] Example 4

[0168] Example 4 differs from Example 1 in that 3 g of C having a purity of 99.9 wt % and a particle size distribution of D is used. 90 Graphite with a size of 20 μm (supplied by Imerys) was used instead of Kish graphite as the exfoliable graphene-based material. In addition, instead of Kish graphite, graphite was mixed with the silicon-graphene composite material.

[0169] Silicon particles and graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 4 (80:20). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 5:95 to solvent and a solids content of 26%.

[0170] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 15 g of silicon-graphene composite material in 44.24 g isopropanol were obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0171] Then 15 g of silicon-graphene composite material dispersed in 44.24 g of isopropanol was mixed with 60 g of graphite (purity 99.9 wt % C, D 90 20μm, D 50 10 μm, nanoplatelet shape, supplied by Imerys) were aggregated at a graphite / composite weight ratio of 4 (80:20), which corresponds to a carbon / silicon ratio of 5.25 (84:16). 120 mL of isopropanol was added to achieve a -1 Viscosity at shear rate 152.16 Pa·s. Therefore, the solids content is 29.4%.

[0172] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-4 wt% graphene-80 wt% graphite composite.

[0173] The obtained 16 wt % organosilicon-4 wt % graphene-80 wt % graphite composite material was tested under the same conditions as in Example 1.

[0174] Table 4 summarizes the results obtained:

[0175]

[0176] Table 4

[0177] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0178] As can be seen, the electrode shows very good performances, such as a FCE of 83% and a capacity of 790 mAh / g active material, thanks to the composite material prepared by the method according to the present invention.

[0179] Example 5

[0180] The difference between Example 5 and Example 1 is that the weight ratio of silicon to organic solvent in the second step is different. The mixing conditions are also different.

[0181] 12 g of silicon particles and 3 g of Kish graphite in isopropanol were gathered together at a silicon / graphite weight ratio of 4 (80:20). 172 g of isopropanol was added. Thus, the weight ratio of silicon to organic solvent was 5:95, the weight ratio of exfoliable graphene-based material to solvent was 1:99, and the solid content was 6.9%.

[0182] The composition was high shear mixed in a Silverson L5 mixer at 3000 rpm for 30 minutes. 15 g of silicon-graphene composite material in 217.4 g isopropanol was obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0183] 15 g of the silicon-graphene composite material dispersed in isopropanol was then aggregated with 60 g of Kish graphite in a graphite / composite weight ratio of 4 (80:20), which corresponds to a carbon / silicon ratio of 5.25 (84:16). No isopropanol was added. The solid content was therefore 25.8%. The Kish graphite had been cleaned in a previous step to a purity of 99.9 wt. % C, having a particle size distribution D of 20 μm. 90 , 10μm particle size distribution D 50 and nanosheet shapes.

[0184] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-4 wt% graphene-80 wt% graphite composite.

[0185] The obtained 16 wt % organosilicon-4 wt % graphene-80 wt % graphite composite material was tested under the same conditions as in Example 1.

[0186] Table 5 summarizes the obtained results:

[0187]

[0188] Table 5

[0189] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0190] As can be seen, the electrode shows very good performances, such as a FCE of 83% and a capacity of 803 mAh / g active material, due to the composite material prepared by the method according to the present invention.

[0191] Example 6

[0192] Example 6 differs from Example 4 in that the obtained 16 wt % organosilicon-4 wt % graphene-80 wt % graphite composite material is further heat treated at 850° C. for 3 hours under argon.

[0193] The heat treated composite material was tested under the same conditions as in Example 1.

[0194] Table 6 summarizes the results obtained:

[0195]

[0196] Table 6

[0197] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0198] The additional heat treatment reduces the oxidation of silicon and homogenizes the composite material distribution. It improves the conductivity and stability of the anode.

[0199] Comparative Example 1

[0200] Supply the following raw materials:

[0201] -810 g of 99% purity and particle size distribution D 50 200μm silicon particles

[0202] - 270 g of a purity of 99 wt% C and a particle size distribution of D 90 The expanded graphite (EG) is 20 μm.

[0203] The expanded graphite was first exfoliated seven times in a three-roll mill (Bühler Trias-300) in gap mode with isopropanol to an initial solid content of 17%. The silicon particles were pre-ground in a bead mill (Bühler PML2 Centex S2SiC) at 1,450 kWh / t and then finely ground in a bead mill (Bühler MicroMedia MMX1) at 30,000 kWh / t to obtain a particle size distribution of 150 nm. 90 and 85nm D 50 The exfoliated expanded graphite was then added to the silicon particles in a Bühler PML2 Centex S2 SiC mill with 4.66 Kg of isopropanol, corresponding to a solid content of 20.7%, a weight ratio of Si to exfoliable graphene-based material of 75:25, a weight ratio of silicon to organic solvent of 16:84, and a weight ratio of exfoliable graphene-based material to solvent of 5:95. The exfoliated expanded graphite and silicon particles in isopropanol were mixed in a bead mill at a tip speed of 11.1 m / sec for 1.25 hours and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 75 wt% silicon-25 wt% graphene composite.

[0204] To test the performance of this active material, it was mixed with lithium polyacrylate (LiPAA) and carbon black C45 in a ratio of 80:10:10 in water in a disperser Dispermat LC-30 at 5000 rpm for 1 hour. The obtained ink was then applied to a copper foil using a doctor blade to form a 100 μ thick wet coating. It was dried in a vacuum oven at 80 ° C for 12 hours. The dry coating was 70 μ thick.

[0205] Electrodes made from coated copper foil were tested in coin cells as half-cells against lithium under the following conditions:

[0206] - Electrolyte: 1 mol / L lithium hexafluorophosphate (LiPF6) in a solvent containing 3:7 volume ratio of fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) and 2 wt% vinylene carbonate (VC),

[0207] - Cycle Scheme:

[0208] ○ Repeated relative to Li / Li + The cell was cycled once at a constant current at a rate of C / 5 in a voltage window of 0.05 V to 0.9 V, and once at a constant voltage at a maximum current rate of C / 10.

[0209] Table 7 summarizes the results obtained:

[0210]

[0211] Table 7

[0212] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0213] As can be seen, when silicon particles and graphene are prepared separately and not mixed with graphite, good performance is not achieved. In addition, the process is expensive, energy inefficient, time consuming, and the silicon particles are not well contained in the carbon matrix.

[0214] Comparative Example 2:

[0215] Supply the following raw materials:

[0216] -4 g of 0.21 g / mL dispersed in isopropanol with a purity of more than 99% and a particle size distribution of D 90 Silicon particles below 291 nm, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0217] -4 g of a purity of 99.9 wt% C and a particle size distribution of D 90 The graphite is 20 μm (supplied by Imerys).

[0218] Silicon particles and graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 1 (50:50). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 21:79 to solvent and a solids content of 37%.

[0219] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 8 g of silicon-graphene composite material in 13.5 g of isopropanol were obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0220] Then 8 g of silicon-graphene composite material dispersed in 13.5 g of isopropanol was mixed with 17 g of graphite (purity 99.9 wt % C, D 90 20μm, D 50 10 μm, nanoplatelet shape, supplied by Imerys) were aggregated at a graphite / composite weight ratio of 2.12 (68:32), which corresponds to a carbon / silicon ratio of 5.25 (84:16). 57 mL of isopropanol was added.

[0221] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-16 wt% graphene-68 wt% graphite composite.

[0222] The obtained 16 wt % organosilicon-16 wt % graphene-68 wt % graphite composite material was tested under the same conditions as in Example 1.

[0223] Table 8 summarizes the results obtained:

[0224]

[0225] Table 8

[0226] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0227] As can be seen, when the weight ratio of silicon / exfoliable graphene-based material is lower than 1.5 (60:40), the performance of the electrode is unsatisfactory. In particular, the cyclability at 80% of the initial capacity retention is limited to 30 cycles.

[0228] Comparative Example 3:

[0229] Supply the following raw materials:

[0230] -4 g of 0.21 g / mL dispersed in isopropanol with a purity of more than 99% and a particle size distribution of D 90 Silicon particles below 291 nm, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0231] - 0.21 g of a purity of 99.9 wt% C and a particle size distribution of D 90 The graphite is 20 μm (supplied by Imerys).

[0232] Silicon particles and graphite in isopropanol were aggregated together at a weight ratio of silicon / graphite of 19 (95:5). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 2:98 to solvent and a solids content of 24%.

[0233] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 4.21 g of silicon-graphene composite material in 13.5 g isopropanol were obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0234] Then 4.21 g of silicon-graphene composite material dispersed in 13.5 g of isopropanol was mixed with 20.79 g of graphite (purity 99.9 wt % C, D 90 20μm, D 50 10 μm, nanoplatelet shape, supplied by Imerys) were aggregated at a graphite / composite weight ratio of 2.12 (68:32), which corresponds to a carbon / silicon ratio of 5.25 (84:16). 62 mL of isopropanol was added.

[0235] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes and then dried in a rotary evaporator at 60°C under vacuum for 1 hour to obtain a 16 wt% silicone-0.842 wt% graphene-83.158 wt% graphite composite.

[0236] The obtained 16 wt % silicone-0.842 wt % graphene-83.158 wt % graphite composite material was tested under the same conditions as in Example 1.

[0237] Table 9 summarizes the results obtained:

[0238]

[0239] Table 9

[0240] n: number of cycles. FCE: first coulombic efficiency. CE n10 : Coulombic efficiency at cycle number 10

[0241] As can be seen, when the weight ratio of silicon / exfoliable graphene-based material is higher than 9 (90:10), the performance of the electrode is unsatisfactory. In particular, the cyclability at 80% of the initial capacity retention is limited to less than 80 cycles.

[0242] Effect of mixing duration on the obtained silicon-graphene composites

[0243] Supply the following raw materials:

[0244] - 4 g of silicon particles with a purity higher than 99% and a particle size distribution D90 lower than 291 nm dispersed in isopropanol at 0.21 g / mL, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0245] 1 g of Kish graphite cleaned in a previous step to a purity of 99.9 wt. % C. The Kish graphite has a particle size distribution D90 of 20 μm.

[0246] Silicon particles and Kish graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 4 (80:20). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 5:95 to solvent and a solids content of 26%.

[0247] The compositions were mixed in a disperser Dispermat LC-30 at 3350 rpm for different durations under high shear. The homogeneity of the mixtures was then observed by SEM.

[0248] Table 10 summarizes the results obtained:

[0249]

[0250] Effect of mixing speed on obtaining silicon-graphene composites

[0251] Supply the following raw materials:

[0252] - 4 g of silicon particles with a purity higher than 99% and a particle size distribution D90 lower than 291 nm dispersed in isopropanol at 0.21 g / mL, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0253] 1 g of Kish graphite cleaned in a previous step to a purity of 99.9 wt. % C. The Kish graphite has a particle size distribution D90 of 20 μm.

[0254] Silicon particles and Kish graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 4 (80:20). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 5:95 to solvent and a solids content of 26%.

[0255] The compositions were mixed in a Dispermat LC-30 for 30 minutes at different speeds under high shear. The homogeneity of the mixtures was then observed by SEM and EDX.

[0256] Table 11 summarizes the results obtained:

[0257]

[0258] Effect of viscosity on mixing of graphite and silicon-graphene composites

[0259] Supply the following raw materials:

[0260] - 4 g of silicon particles with a purity higher than 99% and a particle size distribution D90 lower than 291 nm dispersed in isopropanol at 0.21 g / mL, corresponding to a weight ratio of silicon to organic solvent of 21:79, and

[0261] 1 g of Kish graphite cleaned in a previous step to a purity of 99.9 wt. % C. The Kish graphite has a particle size distribution D90 of 20 μm.

[0262] Silicon particles and Kish graphite in isopropanol were aggregated together at a silicon / graphite weight ratio of 4 (80:20). This was done without further addition of isopropanol. Thus, the exfoliable graphene-based material had a weight ratio of 5:95 to solvent and a solids content of 26%.

[0263] The composition was mixed in a disperser Dispermat LC-30 at 3350 rpm for 30 minutes. 5 g of silicon-graphene composite material in 14.7 g isopropanol were obtained. The Si nanoparticles of the composite material had a size distribution D50 of 70 nm.

[0264] Then 5 g of silicon-graphene composite material dispersed in 20.2 g of isopropanol was aggregated with 20 g of Kish graphite at a graphite / composite weight ratio of 4 (80:20) (which corresponds to a carbon / silicon ratio of 5.25 (84:16)). Kish graphite had been cleaned in a previous step to reach a purity of 99.9 wt % C, with a particle size distribution D90 of 20 μm, a particle size distribution D50 of 10 μm and a nanoplate shape. Different amounts of isopropanol were added to reach different viscosities.

[0265] The mixture was mixed in a Kakuhunter SK-350TII mixer for 5 minutes. When a single phase was obtained, the viscosity was measured at room temperature using a viscometer IKA Rotavisc hi-vi I. The homogeneity of the mixture was observed with the naked eye and / or by SEM.

[0266] Table 12 summarizes the results obtained:

[0267]

[0268] As can be seen from the results, controlling the viscosity of the mixture of silicon-graphene composite material and graphite is the key to obtaining a homogeneous mixture. Insufficient dilution and excessive dilution prevent the mixture from becoming homogeneous.

Claims

1. A method for making a silicon-graphene-graphite composite material for a silicon-based anode for a lithium-ion battery, comprising: -(i) Supply particle size distribution D 10 Silicon particles larger than 100 nm, exfoliable graphene-based materials comprising at least 85 wt. % carbon, - (ii) aggregating the silicon particles and the exfoliable graphene-based material together in a first organic solvent, the weight ratio of silicon to the exfoliable graphene-based material being 1.5 to 9, - (iii) mixing the composition of step (ii) at at least 500 rpm for at least 20 minutes to grind the silicon particles into nanoparticles, to exfoliate at least a portion of the exfoliable graphene-based material into graphene and to form a silicon-graphene composite material, -(iv) aggregating the silicon-graphene composite material and graphite, wherein the weight ratio of carbon to silicon is 1.5 to 19, and the viscosity is within 1 second -1 The shear rate is 0.025Pa·s to 160Pa·s, - (v) mixing the composition of step (iv) for at least 2 minutes to form a silicon-graphene-graphite composite material.

2. The method of claim 1, wherein the exfoliable graphene-based material is selected from the group consisting of graphite, intercalated graphite, expanded graphite, graphite oxide, reduced graphite oxide, graphene oxide, reduced graphene oxide, and mixtures thereof.

3. The method according to any one of claims 1 or 2, wherein the first organic solvent is selected from isopropanol, ethanol and mixtures thereof.

4. The method according to any one of claims 1 to 3, wherein the weight ratio of silicon to the first organic solvent is lower than 0.

66.

5. The method according to any one of claims 1 to 4, wherein step ii) and step iii) are performed simultaneously.

6. The method according to any one of claims 1 to 5, wherein at the end of step iii), the particle size distribution D of the Si particles is 50 Up to 70nm.

7. The method according to any one of claims 1 to 6, wherein the graphite of step iv) has a particle size distribution D below 20 μm. 90 and particle size distribution D below 10 μm 50 .

8. The method according to any one of claims 1 to 7, wherein the graphite of step iv) is battery grade graphite.

9. The process according to any one of claims 1 to 8, wherein a second solvent is added in step iv).

10. The method according to any one of claims 1 to 9, wherein: In step iv) and step v), the solid content is maintained above 11%.

11. The method according to any one of claims 1 to 10, wherein: In step v), mixing is continued for less than 20 minutes.

12. A silicon-graphene-graphite composite material for a silicon-based anode of a lithium-ion battery, comprising: - Particle size distribution D wrapped in graphene layer 50 Silicon particles up to 70nm in size, - graphite particles having a weight ratio of carbon to silicon of 1.5 to 19, - a first organic solvent, The viscosity of the silicon-graphene-graphite composite material is 1 second -1 The shear rate is 0.025 Pa·s to 160 Pa·s.

13. An active material for a silicon-based anode of a lithium-ion battery, comprising silicon-graphene - A graphite composite material, the silicon-graphene-graphite composite material comprising: - Silicon particles with a particle size distribution D50 up to 70 nm encapsulated in graphene layers, - Graphite particles having a carbon to silicon weight ratio of 1.5 to 19.

14. A silicon-based anode for a lithium-ion battery comprising the active material according to claim 13.

15. A lithium ion battery comprising the silicon-based anode according to claim 14.